Dynamics of particle transport from soils to the sea - Don E. Canfield; Amin Naemi (Royal Society Open Science)
In this study, we explore the fate of soils, from their erosion into rivers to their final deposition as either continental or marine deposits. We focus on the continental United States and compare the chemistries of river suspended and bottom sediment with the chemistry of the surface soils from which these particles originate. We find that river bottom sediment is closer to the chemical composition of soils than to suspended sediment, implying that a large fraction of surface soils end up as river bottom sediment. We identify Zr/Al as a robust tool to differentiate river suspended and bottom sediment, and we use this tool to calculate that in the rivers studied, ca 60% of weathered rock mass ends as river bottom sediments and ca 40% is transported as suspended load. The Zr/Al ratio of marine sediments is close to the ratio in river suspended sediments, and we calculate that marine sediments comprise greater than 90% river suspended material. Overall, through the pre-Anthropogenic Holocene, approximately 50% of the particles eroded from the soils of continental United States accumulate in continental deposits, with the rest being transported to the sea. The principles outlined here could prove useful in exploring the dynamics of soil transport to the sea in the geologic past.